Controle de sistemas max-plus lineares sujeitos a restrições no estado: aplicação a sistemas de transporte - Cintia Ribeiro Andrade (2008)
This thesis deals with the modeling and control of discrete events systems subject to synchronization and time delay phenomena. These systems are non-linear in conventional algebra, but can be described in a linear way using the max-plus algebra. The objective of this thesis is to design a controller that guarantees that the system will evolve without violating timed restrictions imposed to the state. In this sense, a sufficient condition which guarantees the existence and computation of the controller is obtained. To illustrate the contribution of this work, an urban traffic network is presented, in which the controller is designed in order to guarantee that temporization restrictions are respected.